2014
DOI: 10.1093/mnrasl/slu067
|View full text |Cite
|
Sign up to set email alerts
|

The first analytical expression to estimate photometric redshifts suggested by a machine

Abstract: We report the first analytical expression purely constructed by a machine to determine photometric redshifts (z phot ) of galaxies. A simple and reliable functional form is derived using 41, 214 galaxies from the Sloan Digital Sky Survey Data Release 10 (SDSS-DR10) spectroscopic sample. The method automatically dropped the u and z bands, relying only on g, r and i for the final solution. Applying this expression to other 1, 417, 181 SDSS-DR10 galaxies, with measured spectroscopic redshifts (z spec ), we achiev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 31 publications
0
15
0
1
Order By: Relevance
“…models [22], template fitting methods [23], and other schemes and analyses [24], [25]. Feature selection schemes have been successfully applied as well in this context [26], [27], [28] and, in particular, using linear models for photometric redshift estimation [29]. We are, however, not aware of any approaches conducting exact feature selection for linear regression in this context.…”
Section: Applicationmentioning
confidence: 99%
“…models [22], template fitting methods [23], and other schemes and analyses [24], [25]. Feature selection schemes have been successfully applied as well in this context [26], [27], [28] and, in particular, using linear models for photometric redshift estimation [29]. We are, however, not aware of any approaches conducting exact feature selection for linear regression in this context.…”
Section: Applicationmentioning
confidence: 99%
“…Initially the training set was used to map a polynomial function between the colors and the redshift (e.g., Connolly et al, 1995;Brunner et al, 1997). More recently, this process has been extended to machine learning algorithms, including artificial neural networks (e.g., Collister & Lahav, 2004;Oyaizu et al, 2008b;Bonnett, 2013), boosted decision trees (e.g., Gerdes et al, 2010), random forest (e.g., Carliles et al, 2010;Carrasco Kind & Brunner, 2013c), nearest neighbors (e.g., Ball et al, 2007Ball et al, , 2008Lima et al, 2008), spectral connectivity analysis (e.g., Freeman et al, 2009), Gaussian process (e.g., Way et al, 2009;Bonfield et al, 2010), support vector machines (e.g., Wadadekar, 2005), Quasi Newton Algorithm (e.g., Cavuoti et al, 2012;Brescia et al, 2014), and from analytical forms suggested by computational algorithms (e.g., Schmidt & Lipson, 2009;Krone-Martins et al, 2014). While only a few of these photo-z methods are publicly available, they all perform to a similar accuracy and provide only a single redshift estimate rather than a full redshift probability density function for each galaxy.…”
Section: Machine Learning Techniquesmentioning
confidence: 99%
“…Crisci et al 2012;Libbrecht & Noble 2015;Vidyasagar 2015). Following this trend, the present work is an additional effort to popularize modern machine learning techniques within astronomy (see Ball & Brunner 2010;Krone-Martins et al 2014;Ivezic et al 2014, and references therein).…”
mentioning
confidence: 93%